Internet Marketing and Structural Changes e-Commerce in Ukraine - Kolodynskyi, S.; Hutsaliuk, O.; Kramskyi, S.; Zakharchenko, O. (Економічний вісник Донбасу, 2022)
Abstract. The article reveals the essence of Internet marketing as a universal scientific and methodological tool and a complex system of information technologies, which are extremely necessary for the functioning of modern business entities in markets with different structures and dynamics of development. The structure of Ukraine's economy is under the influence of complex global economic relations, and there is an acute problem of applying universal information technologies to determine the direction of the country's development, its inclusion in a complex system of trade relations on world markets, and to withstand competition with global trading companies. Under such difficult conditions, both internal and external, the role of Internet marketing in strengthening, first of all, trade interaction between the regions of the country for the further exit of domestic product manufacturers to world markets is growing sharply. Purpose and tasks. The purpose of the article is to determine the main components of the influence of Internet marketing on modern commercial processes in the national economy and to establish structural changes in the field of trade in various goods on the national market of Ukraine. Electronic commerce is gaining widespread use in the world and is becoming a cornerstone in the formation of global economic ties between the countries of the world, to which Ukraine is also advancing. However, a number of difficulties on this path become an obstacle to the commercialization of economic relations between domestic enterprises and advanced countries of the world. Materials and methods. All theoretical conclusions and results of the article are based on the scientific methods of researching the processes of digitalization of economic opportunities, which were based on the provisions of classical economic theory, modern theories of the development of scientific and technological progress. The research methodology is based on the principles of a systematic approach to the analysis of the essence of Internet marketing and the process of restructuring trade relations using the Internet, analysis of the role and place of electronic commercial activity in modern national economic systems, which are transformative and structurally deformed systems based on Internet technologies. In the course of the study, logical, empirical methods of learning the mechanisms and forms of e-commerce management were used, as well as methods of comparative, factorial, situational, economic and statistical analysis, forecasting of the restructuring process, grapho-analytical and algorithmic methods of displaying the obtained research results, software methods and modern information and computer technologies. Priorities in the use of this or that method were determined by the tasks and the purpose of scientific research. The results. The conducted research reflected the complexity and difficulty of the processes of spreading digital technologies in the economic environment of Ukrainian enterprises. Digitization as a technology characteristic of modern high-tech enterprises affects all spheres of their activity, especially the sphere of commercialization of the results of enterprise activity. The implementation of the product produced and offered for use covers a large number of Ukrainian enterprises and they need the development of Internet marketing, which gives significant advantages to enterprises in the markets. Such advantages include the processes of creating permanent groups of consumers, forming focus groups of consumers, reducing the costs of promoting goods to consumers, using advertising as a tool for forming needs and providing many other advantages, which are indicated in the article. An important result of the conducted research was the analysis of the state and directions of Internet marketing development in the modern Ukrainian economy. The article indicates the main directions of the formation of electronic commerce and the influence of Internet marketing on this process. Conclusions. The result of the article is an assessment of the economic efficiency of Internet marketing at the current stage of the structural deformation of e-commerce in Ukraine. The increase in the volume and dynamics of electronic trade shows the importance of this type of activity for Ukrainian enterprises and strengthens the global economic ties between the enterprises of our country and the commercial enterprises of the leading countries of the world.